A study on the relationship between work environment and job performance among support staffs in selected government offices injalan badlishah, Kedah Darul Aman / Nur Asmira Johari - Johari, Nur Asmira (Faculty of Business Management, 2018)
This correlation research was carried out to study the relationship between work environments and job performance among support staffs in selected government offices in Jalan Badlishah, Kedah Darul Aman. Survey questionnaires which were adopted from Susan, Bajaj, Rosner, Lockley & Schembammer (2012) and Kenny (2015) has been distributed to the respondents, who worked as support staff and yield 100% response rate. A total of 103 support staffs in selected government offices which were working at Pejabat Pendidikan Daerah Kuala MudalYan (PPD KMY) and Kementerian Perdagangan Dalam Negeri, Koperasi dan Kepenggunaan (KPDNKK) in Jalan Badlishah, Kedah Darul Aman participated in the research. This study used a stratified random sampling techniques and the sample size was determined using Krejcie and Morgan (1970). The Questionnaires were analyzed using SPSS version 20. Most of the respondents were female, aged 31 until 40 years old and from grade C support staff. There was a strong relationship between work environment and job performance (r=0.71, p=O.OO). However, the findings also showed that the correlation was significant as a result for lighting (r=0.5 I, p=O.OO) and work stress (r=0.62, p=O.OO). The value of R-Square showed that 50% of the variance in work environment can be predicted from the variables of lighting and work stress. The result revealed that there was a significant relationship between lighting with job performance among support staffs. It is recommended that organization should improve support staff’s welfare, provide a training or workshop and improve support staff’s motivation. Future research should provide a healthy working environment as this not only benefit the support staffs but also increase the efficiency and effectiveness of the selected government offices